Reconceptualizing Islamic Law in Regulating Contemporary Society: A Legal and Social Perspective - Desty Endrawati Subroto (Edujavare Publishing, 2026)
This study examines the role of Islamic law in contemporary society, focusing on its principles, applications, and challenges in modern legal and social systems. The research employs a normative legal method with conceptual and doctrinal approaches based on secondary data from Islamic legal texts, academic literature, and institutional reports. The findings indicate that Islamic law regulates contemporary society through principles of justice, welfare, and ethical responsibility, implemented in areas such as finance, family law, and social welfare. However, challenges such as differing interpretations, globalization, and legal pluralism affect its implementation. The study concludes that Islamic law remains a dynamic and relevant legal system capable of addressing modern societal needs when supported by strong scholarly interpretation and institutional development